Sustainable Natural and Synthetic fibers with Epoxy Composites of Mechanical Characterization and One-Way ANOVA Statistical Analysis - Kemparaju, Sadashiva; Rangaswamy, Bhanu Prathap; Javaraiah, Balaji; Mahadev, Shwetha; Murugan, Rathika; Jane, Tarakeshwar (Engineering Transactions, 2025)
It is now well recognized that the combination of natural and synthetic fibers in synergistic fiber composite materials can greatly broaden their applications in engineering and technology. Natural-fibers are gaining more consciousness because of their biodegradability, easy availability, durability, and resistance to corrosion, positioning them as an eco-friendly substitute for conventional materials. At the same time, fiber-reinforced composites are increasingly replacing metals in multiple sectors owing to their cost-effectiveness and energy efficiency. Epoxy resin-based hybrid composites were prepared by incorporating glass, hemp and ramie fibers through the hand layup approch. Laminates were characterized for tensile, flexural, impact, and hardness performance using ASTM standard methods. The greatest tensile strength, 73.10 MPa, was achieved in the glass/ramie fiber composite. The hybrid composites comprising glass, ramie, and hemp fibers exhibited enhanced flexural behavior of 18.22 MPa, impact resistance of 142.45 kJ/m². Among the tested configurations, the glass–ramie fiber composite recorded the highest hardness value of 27.73 HV. Overall, the determination highlight that glass-ramie-hemp fiber-mixed epoxy composite materials can serve as prospective eco-friendly substitute to conventional synthetic composites in non-structural applications, such as automotive interiors, by offering a balance of good mechanical performance and sustainability.